Hypertrophy of the Anterior External Arcuate Fasciculus: A Rare Variant With Implications for the Development of the Arcuate Nucleus - Renee Stonebridge; Renee Stonebridge; Ross J. Taliano; Ross J. Taliano; Terra D. Velilla; Douglas C. Anthony; Douglas C. Anthony; Douglas C. Anthony (Frontiers Media S.A., 2020)
A rare anatomic variant of a markedly enlarged anterior external arcuate fasciculus (AEAF) on the ventral medullary surface is reported and compared to two controls. The hypertrophic AEAF was nine times larger in diameter than normal, whereas the arcuate nucleus (AN) and inferior olivary nucleus (ION) appeared histologically normal in size and neuronal distribution, and morphometric analysis of the AN confirmed that it was within the normal range. Calbindin-2 (calretinin, CALB2) expression was identified in the AN and in the fibers of the normal AEAF. The hypertrophic AEAF did not contain calbindin-2-expressing fibers. CALB2 expression was also present in the ventrolateral portion of the ION, both in the index case and in one of the control cases. The origin of the additional fibers was not identified; however, the potential origin of these fibers and its implications for the development of the AEAF are discussed.